Pacific Southwest United States Holocene Droughts and Pluvials Inferred From Sediment δ18O(calcite) and Grain Size Data (Lake Elsinore, California) - Kirby, Matthew Edward Christopher; Patterson, William Paul; Lachniet, Matthew; Noblet, James A.; Anderson, Michael A.; Nichols, Kevin; Avila, Judith (Frontiers in Earth Science, 2019)
Records of past climate can inform us on the natural range and mechanisms of climate change. In the arid Pacific southwest United States (PSW), which includes southern California, there exist a variety of Holocene records that can be used to infer past winter conditions (moisture and/or temperature). Holocene records of summer climate, however, are rare from the PSW. In the future, climate changes due to anthropogenic forcing are expected to increase the severity of drought in the already water stressed PSW. Hot droughts are of considerable concern as summer temperatures rise. As a result, understanding how summer conditions changed in the past is critical to understanding future predictions under varied climate forcings. Here, we present a c. 10.9 kcal BP 18O(calcite) record from Lake Elsinore, California, interpreted to reflect 18O(lake water) values as controlled by over-water evaporation from summer-to-early fall. Our results reveal three millennial scale intervals: 1) the highly evaporative Early Holocene (10.55-6.65 kcal BP), 2) the less evaporative Mid-Holocene (6.65-2.65 kcal BP); and, 3) the evaporative Late Holocene (2.65-0.55 kcal BP). These results are coupled with an inferred winter precipitation runoff (sand content) record from Kirby et al. (2010). Using these data together, we estimate the duration and severity of centennial-scale Holocene droughts and pluvials (e.g., high 18O(calcite) values plus low sand content = drought and vice versa). Furthermore, the coupled 18O(calcite) and sand data provide a generalized Holocene lake level history. The most severe, long-lasting droughts (i.e., maximum summer-to-early fall evaporation and minimum winter precipitation runoff) occur in the Early Holocene. Fewer, less severe, and shorter duration droughts occurred during the Mid-Holocene as pluvials became more common. Droughts return with less severity and duration in the Late Holocene. Notably, the Little Ice Age is characterized as the wettest period during the Late Holocene.